The Effect of Internal Audit on Business Performance in Industrial Enterprises and a Survey Study - Yılmaz Uzun; Sinan Aslan (Muhasebe Enstitüsü Dergisi)
Focusing on providing added value to the organization by examining and improving business operations, the primary goal of internal audit is to help achieve business objectives. Business performance is generally expressed as the level of success shown in reaching the goals. . In this direction, the main purpose of the study is to determine the relationship between internal audit and business performance in industrial enterprises. In this context, it was examined whether the senior management’s support, the internal audit’s independence, the internal auditors’ professional competencies and the internal control system have an effect on the financial performance (return on assets, return on equity and net profit margin). In the study, the data obtained through applicaiton of a questionnaire on the manufacturing industrial enterprises in Borsa Istanbul were analyzed with Kruskal-Wallis H Test, a non-parametric method via SPSS (Version 26). As a result of the analysis; it has been determined that the return of asssets had a significant relationship with senior management support, professional competence and internal control system; and a non-significant relationship with the independence of internal audit. It has also been determined that the return on equity had a significant relationship with senior management support, professional competence and internal control system; and a non- significant relationship with the independence of internal audit. Also, a non-significant relationship was detected between net profit margin and senior management support, professional competence, internal control system and the independence of internal audit.